Uncoupled pyroptosis and IL-1β secretion downstream of inflammasome signaling - Li, Yang; Jiang, Qianzhou (Frontiers in Immunology, 2023)
Inflammasomes are supramolecular platforms that organize in response to various damage-associated molecular patterns and pathogen-associated molecular patterns. Upon activation, inflammasome sensors (with or without the help of ASC) activate caspase-1 and other inflammatory caspases that cleave gasdermin D and pro-IL-1β/pro-IL-18, leading to pyroptosis and mature cytokine secretion. Pyroptosis enables intracellular pathogen niche disruption and intracellular content release at the cost of cell death, inducing pro-inflammatory responses in the neighboring cells. IL-1β is a potent pro-inflammatory regulator for neutrophil recruitment, macrophage activation, and T-cell expansion. Thus, pyroptosis and cytokine secretion are the two main mechanisms that occur downstream of inflammasome signaling; they maintain homeostasis, drive the innate immune response, and shape adaptive immunity. This review aims to discuss the possible mechanisms, timing, consequences, and significance of the two uncoupling preferences downstream of inflammasome signaling. While pyroptosis and cytokine secretion may be usually coupled, pyroptosis-predominant and cytokine-predominant uncoupling are also observed in a stimulus-, cell type-, or context-dependent manner, contributing to the pathogenesis and development of numerous pathological conditions such as cryopyrin-associated periodic syndromes, LPS-induced sepsis, and Salmonella enterica serovar Typhimurium infection. Hyperactive cells consistently release IL-1β without LDH leakage and pyroptotic death, thereby leading to prolonged inflammation, expanding the lifespans of pyroptosis-resistant neutrophils, and hyperactivating stimuli-challenged macrophages, dendritic cells, monocytes, and specific nonimmune cells. Death inflammasome activation also induces GSDMD-mediated pyroptosis with no IL-1β secretion, which may increase lethality in vivo. The sublytic GSDMD pore formation associated with lower expressions of pyroptotic components, GSDMD-mediated extracellular vesicles, or other GSDMD-independent pathways that involve unconventional secretion could contribute to the cytokine-predominant uncoupling; the regulation of caspase-1 dynamics, which may generate various active species with different activities in terms of GSDMD or pro-IL-1β, could lead to pyroptosis-predominant uncoupling. These uncoupling preferences enable precise reactions to different stimuli of different intensities under specific conditions at the single-cell level, promoting cooperative cell and host fate decisions and participating in the pathogen “game”. Appropriate decisions in terms of coupling and uncoupling are required to heal tissues and eliminate threats, and further studies exploring the inflammasome tilt toward pyroptosis or cytokine secretion may be helpful.